Maternal health disparities in district Jhansi, Uttar Pradesh: a time series analysis using health management information system records - Gupta, Arjita; Raj, Utsav (International Journal Of Community Medicine And Public Health, 2023)
This study focused on investigating the status of maternal health in Jhansi District, Uttar Pradesh, India. A comprehensive analysis of data obtained from the health management information system (HMIS) spanning the period from 2010 to 2020. The findings of this study indicate notable fluctuations in the percentage of first-trimester ANC registrations, accompanied by an overall improvement in compliance with the recommended number of ANC checkups. In addition, the study identifies a growing inclination towards institutional deliveries and increased utilization of cesarean section (C-section) procedures. This study emphasizes the urgent and continued implementation of measures to enhance timely access to ANC services and to ensure the presence of skilled birth attendants during all childbirths. These insights are of substantial significance to policymakers and healthcare providers in their efforts to advance maternal healthcare services, diminish maternal mortality rates, and enhance women’s overall well-being in Jhansi District, Uttar Pradesh, India. The study recommends reinforcing ANC services, promoting collaborative initiatives to improve maternal health outcomes, and establishing clear guidelines and regular quality audits to ensure the appropriate utilization of C-sections.